HIPERCONECTADOS: Perfil e comportamento dos nativos digitais - Cirilo, Reinaldo de Sá (2019)
The theme of this research is the hyperconnection and the transformations that contemporary society has been suffering due to the technological impacts and the exorbitant amount of information to which it is exposed. Our object of study is the world of so-called digital natives, the first generation to live an entirely digital and connected life. The main objective of this work is to understand (in the sense of embracing, integrating, including) the most striking features of the profile and behavior of this generation, which we call the Z generation. Methodologically, this is an exploratory research that is constructed from an attentive study of this subject in specialized bibliography, in scientific texts presented at events such as those of Compós - the National Association of Postgraduate Programs in Communication and the ABCiber - the Brazilian Association of Researchers in Cyberculture, publications in magazines and books in the communication area, research and statistical data on the phenomena explored. Recognized with due caution, are the readings of this event, made by scholars who try to make possible predictions of the near or distant future. The conclusions we reached about the profile and behavior of hyperconnected youths result from a historical rescue of technological evolution, including the transition from analog to digital, and from an analysis of what is being called hypermodern times, a time in which these young people live exposed to the Internet and mobile connections, in a process that made them always on individuals.